Structure and functional analysis of the Legionella pneumophila chitinase ChiA reveals a novel mechanism of metal-dependent mucin degradation. - Saima Rehman; Lubov S Grigoryeva; Katherine H Richardson; Paula Corsini; Richard C White; Rosie Shaw; Theo J Portlock; Benjamin Dorgan; Zeinab S Zanjani; Arianna Fornili; Nicholas P Cianciotto; James A Garnett (PLoS Pathogens)
Chitinases are important enzymes that contribute to the generation of carbon and nitrogen from chitin, a long chain polymer of N-acetylglucosamine that is abundant in insects, fungi, invertebrates and fish. Although mammals do not produce chitin, chitinases have been identified in bacteria that are key virulence factors in severe respiratory, gastrointestinal and urinary diseases. However, it is unclear how these enzymes are able to carry out this dual function. Legionella pneumophila is the causative agent of Legionnaires' disease, an often-fatal pneumonia and its chitinase ChiA is essential for the survival of L. pneumophila in the lung. Here we report the first atomic resolution insight into the pathogenic mechanism of a bacterial chitinase. We derive an experimental model of intact ChiA and show how its N-terminal region targets ChiA to the bacterial surface after its secretion. We provide the first evidence that L. pneumophila can bind mucins on its surface, but this is not dependent on ChiA. This demonstrates that additional peripheral mucin binding proteins are also expressed in L. pneumophila. We also show that the ChiA C-terminal chitinase domain has novel Zn2+-dependent peptidase activity against mammalian mucin-like proteins, namely MUC5AC and the C1-esterase inhibitor, and that ChiA promotes bacterial penetration of mucin gels. Our findings suggest that ChiA can facilitate passage of L. pneumophila through the alveolar mucosa, can modulate the host complement system and that ChiA may be a promising target for vaccine development.